Kedudukan Hukum Bagi Pemerintah dalam Kontrak Pengadaan Barang dan Jasa - Tanggahma, Biloka (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This research aims to determine the legal position of the government in contracts for the procurement of goods and services as well as the burden of responsibility for the government in implementing contracts for the procurement of goods and services. The type of research used is normative juridical, namely examining legal concepts related to contracts in general and commercial contracts in particular. In this case, the object of this research is related to the status and authority of the government in contracts for the procurement of goods and services. The research results reveal that sometimes the government is involved in civil relations in the same position as private parties as in contracts for the procurement of goods and services, without its specific position as an institution to protect the public interest. The imposition of government responsibility in implementing contracts for the procurement of goods and services can be viewed from two aspects in terms of the government's actions as one of the parties to the contract for the procurement of goods and services, namely actions that are inherent in government institutions and private (individual) government officials, so that they can be held accountable based on Article 1365 Civil Code. Therefore, the auction/tender committee and/or authorized officials in issuing decisions both in making contracts for the procurement of goods and services and in implementing these contracts must be based on basic values or principles of justice and rational responsibility.